Peran Gereja Dalam Upaya Menghindari Sikap Apatis Teologis Terhadap Kaum Muda: Peran Gereja Dalam Upaya Menghindari Sikap Apatis Teologis Terhadap Kaum Muda - Guntur Hari Mukti; Victor Deak; Meriko Zonnedy Simangunsong (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2023)
Abstract - Many places of worship (church buildings) changed their function because of the lack of visitors and eventually became empty. This phenomenon occurs in many European countries that used to be the center of Christianity. Some have turned into hotels, discotheques, museums, and even places of worship for other religions. This phenomenon does not just happen, one of the contributing factors is the theological apathy of young people, namely an attitude that does not care or does not want to know about matters related to their beliefs. In Indonesia, young people prefer going to places of entertainment rather than attending youth fellowships at church. So that the church cannot remain silent in view of this situation, the church must take action. How can the church overcome the problem of theological apathy among young people? What role can be played so that young people return to having an enthusiastic attitude towards matters related to their beliefs? Seeing this situation, the authors will conduct research with the theme "The Role of the Church in Overcoming Theological Apathy towards Young People." This research was conducted using a qualitative research method, namely through literature studies. In conclusion, the role that the church can play in overcoming theological apathy towards young people is by re-evangelizing and through an exemplary approach in the church; the shepherd as a role model, the parents as an example and the youth themselves as an example for other young people.